Update on Imaging in Posterior Segment Uveitis (2018)
Purpose of Review: Multimodal imaging is required to comprehensively evaluate and follow posterior uveitides. Specific applications of the most commonly used modes of imaging in posterior segment uveitis are described. Recent Findings: Ultra-wide field imaging, fundus autofluorescence, spectral domain optical coherence tomography, and optical coherence tomography angiography are increasingly used to diagnose and follow patients with uveitis. Pertinent findings in the literature are reviewed. Summary: The evaluation of patients with uveitis has been greatly enhanced with the use of different imaging modalities. Both invasive and non-invasive tests provide invaluable information on diagnosis, classification, and disease monitoring leading to better understanding and treatment decisions. © 2018, Springer Science+Business Media, LLC, part of Springer Nature.